unmet dental treatment needs and barriers to dental care of patients with special needs attending a dental teaching hospital - Marchan,Shivaughn Maria (2022)
Abstract Objectives: This work attempted to determine the unmet dental treatment needs and self-reported barriers to continued care, in patients with special needs, attending a dental teaching hospital in the English-speaking Caribbean. Methods: A chart audit of patients who were planned for comprehensive treatment for the period from August 1, 2015 to July 31, 2017 was used to determine the types of treatment required for the sample of patients. Treatment was classified as either urgent, preventive, or restorative. Restorative treatment was further divided into operative, endodontic, periodontic, and prosthodontic treatment. Reasons for not returning to the clinic to complete planned treatment care were ascertained via a telephone interview. A non-parametric McNemar change test for related samples at an alpha level of 0.05 was used to compare planned treatment with completed treatment. Results: 34% of patients with special needs had comprehensive treatment plans developed for the period under investigation. Preventive dental treatment was included in most comprehensive plans (96.1%). Large proportions of patients also required care for periodontal disease (65.7%) and operative management of caries (52.9%). While there was no significant difference between preventive treatment planned and received, there were significant differences in treatment planned and received for all types of restorative care. Major identified barriers included cost, accessibility, and psychosocial issues. Conclusions: There was an unmet need for restorative and periodontal treatment. Major self-reported barriers to dental care included cost, accessibility to care in terms of transportation issues, and psychosocial issues.